Persistence of umbilical artery doppler abnormalities following antenatal corticosteroids: association with perinatal outcome and neurodevelopmental disability at 2 years of age. (7th June 2011) - Sivalingam, V N; Duthie, L B; Wong, C M; Menon, G; Urquhart, J; Cooper, E S; Stock, S J E
Abstract : Background: Administration of antenatal corticosteroids in pregnancies with absent or reversed end-diastolic flow (A/REDF) on umbilical artery Doppler results in transient improvement in flow in two-thirds of pregnancies. It has been hypothesized that persistent abnormalities may be associated with poorer perinatal outcomes. Aim: To determine whether umbilical artery Doppler unresponsiveness to antenatal steroids in growth restricted fetuses is predictive of perinatal outcomes in babies born preterm. Methods: Retrospective cohort study of singleton pregnancies with umbilical artery A/REDF, who had Dopplers performed before and after steroids. Outcomes were compared in pregnancies with and without a response. Cases were identified from ultrasound records. Maternity, neonatal and follow-up records were reviewed. Outcomes included gestation at delivery, birth weight, perinatal mortality and significant neonatal morbidity (bronchopulmonary dysplasia, intracranial haemorrhage, necrotizing enterocolitis and retinopathy of prematurity) and neurodevelopmental disability at 2 years corrected age. Data were analyzed with χ 2 . Results: 46 pregnancies were eligible for inclusion and 2 year paediatric follow-up data available for 28 babies <32 weeks gestation. Mean gestation at delivery was 28 weeks. Corticosteroids were associated with transient improvement in Dopplers in 18/46 (39.1%). Lack of response to steroids was associated with higher rates of composite neonatal morbidity and mortality (56.7% vs 21.4%, p<0.05) and moderate/severe neurodevelopmetal disability at 2 years of age (21% vs 0%, p<0.0001). Conclusion: Transient improvement in EDF was observed less frequently than reported previously. Lack of improvement in EDF appears to be a marker for poorer perinatal outcome and neurodevelopmental disability at 2 years of age.